2019
DOI: 10.1111/rec.13054
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of early outplanting of sexually propagated Acropora verweyi for coral reef restoration demonstrated in the Philippines

Abstract: Over the last 20 years, coral sexual propagation techniques for reef restoration have been steadily developed and improved. However, these techniques involve considerable time and costs to grow coral propagules. There is a need to examine the optimal size of juvenile corals for outplantation. Here, we outplanted sexually propagated small (3-5 mm diameter) and large (10-15 mm diameter) Acropora verweyi corals at 4 months after fertilization at two sites in northwestern Philippines, and compared their survival a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…For instance, in a study investigating the susceptibility of coral recruits to predation by using settlement plates, parrotfish abundance was correlated with coral recruit mortality, attributed to accidental grazing, whereas butterflyfish abundance was correlated with juvenile coral mortality, attributed to predation (Penin et al, 2010). Nonetheless, both survival and growth rates of juvenile corals increase with transplant size and time spent at a nursery prior to transplantation (Guest et al, 2014;Ligson et al, 2020).…”
Section: Corallivorymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in a study investigating the susceptibility of coral recruits to predation by using settlement plates, parrotfish abundance was correlated with coral recruit mortality, attributed to accidental grazing, whereas butterflyfish abundance was correlated with juvenile coral mortality, attributed to predation (Penin et al, 2010). Nonetheless, both survival and growth rates of juvenile corals increase with transplant size and time spent at a nursery prior to transplantation (Guest et al, 2014;Ligson et al, 2020).…”
Section: Corallivorymentioning
confidence: 99%
“…For instance, in a study investigating the susceptibility of coral recruits to predation by using settlement plates, parrotfish abundance was correlated with coral recruit mortality, attributed to accidental grazing, whereas butterflyfish abundance was correlated with juvenile coral mortality, attributed to predation (Penin et al ., 2010). Nonetheless, both survival and growth rates of juvenile corals increase with transplant size and time spent at a nursery prior to transplantation (Guest et al ., 2014; Ligson et al ., 2020). Augmenting the size of juvenile corals ex situ , thus decreasing size‐dependent mortality due to predation, may be preferable when considering optimal transplant size, despite the added maintenance cost (Raymundo & Maypa, 2004; Toh et al ., 2014).…”
Section: Corallivorymentioning
confidence: 99%
“…On the other hand, the size difference between the two size classes of coral juveniles before outplantation was no longer evident 4 years later. However, during the critical early months of outplantation, the larger coral outplant size may offer some survival and growth benefits (Toh et al 2014; Ligson et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The present study aims to determine the long‐term survival and maturity of sexually propagated Acropora verweyi coral colonies and builds on the initial study of Ligson et al (2020). This initial study indicated promising 1‐year survival (29.5%) of 240 A. verweyi sexually reared outplants after only 4 months rearing in ex situ nurseries.…”
Section: Introductionmentioning
confidence: 99%
“…In the initial stages of coral restoration research, direct coral transplantation gained popularity as one approach to rapidly increase coral cover by re-attaching coral fragments or whole colonies to degraded reefs [5,8,9]. As an alternative, an intermediate step of rearing coral nubbins in different types of nurseries increased the number of transplant materials from a few source colonies [10][11][12]. While this grow-out nursery phase increases the size and robustness of coral transplants, which may lead to higher post-transplantation survival rates [13][14][15], it also increases production costs from hatchery and nursery facility construction, grow-out costs, and outplanting costs [5,16].…”
Section: Introductionmentioning
confidence: 99%